2022
DOI: 10.3390/diagnostics12071754
|View full text |Cite
|
Sign up to set email alerts
|

Desquamative Gingivitis in the Context of Autoimmune Bullous Dermatoses and Lichen Planus—Challenges in the Diagnosis and Treatment

Abstract: Desquamative gingivitis (DG) is a clinical term that describes erythema, desquamation and erosions of the gingiva, of various etiologies. Although the clinical aspect is not specific for a certain disease, an accurate diagnosis of the underlying disorder is necessary because the disease course, prognosis and treatment vary according to the cause. DG may inflict significant oral discomfort, which is why patients typically present to the dentist for a first consultation, rendering it important for these speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…A possible explanation of the desquamation is that autoantibodies are directed against molecules such as desmoglein 3, integrin, desmoplakin II and others in the basement membrane of the epithelium causing the lysis of intercellular connections and thus a friable epithelial lining. Other etiologic factors of DG constitute genetic predisposition (DG lesions associated with HLA-B7, metabolic disorders such as diabetes, medication such as NSAIDS or even infections such as those caused by hepatitis C virus (HCV) or hepatitis B virus (HBV) 8 .…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation of the desquamation is that autoantibodies are directed against molecules such as desmoglein 3, integrin, desmoplakin II and others in the basement membrane of the epithelium causing the lysis of intercellular connections and thus a friable epithelial lining. Other etiologic factors of DG constitute genetic predisposition (DG lesions associated with HLA-B7, metabolic disorders such as diabetes, medication such as NSAIDS or even infections such as those caused by hepatitis C virus (HCV) or hepatitis B virus (HBV) 8 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Solomon et al demonstrated that the values of salivary parameters (calcium, phosphates, and pH) were significantly higher in patients with a small number of dental lesions, compared with the patients who had multiple carious lesions [54]. Moreover, oral mucosal conditions such as desquamative gingivitis, autoimmune bullous dermatoses, lichen planus, and symptomatic migratory stomatitis patients may avoid spicy foods, sour drinks, and alcohol, which exacerbate the pain [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of a new drug for a disease could be assessed only in comparison with the standard therapy under standard treatment status. Currently, the dominant and standard treatment of OLP is corticosteroids, and its effect on the relief of signs and symptoms of OLP has been proven in earlier studies (25)(26)(27)(28)(29)(30). However, due to their complications and adverse effects, the continuous use of corticosteroids is limited (31,32).…”
Section: Discussionmentioning
confidence: 99%